2021
DOI: 10.3390/nano11123175
|View full text |Cite
|
Sign up to set email alerts
|

Nelumbo nucifera Seed–Derived Nitrogen-Doped Hierarchically Porous Carbons as Electrode Materials for High-Performance Supercapacitors

Abstract: Biomass-derived activated carbon materials with hierarchically nanoporous structures containing nitrogen functionalities show excellent electrochemical performances and are explored extensively in energy storage and conversion applications. Here, we report the electrochemical supercapacitance performances of the nitrogen-doped activated carbon materials with an ultrahigh surface area prepared by the potassium hydroxide (KOH) activation of the Nelumbo nucifera (Lotus) seed in an aqueous electrolyte solution (1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Figure 6a shows the GCD profiles of all the samples at 1 A g −1 , including the reference carbon, which are of triangular form confirming an EDLC-type charge storage mechanism. From the above result, we see that the reference sample MxP-500 shows the lowest charge discharge time whereas the MxC-Z700 shows the highest charge discharge time which confirms the maximum charge storage capacity because of the nanoporous structure [30][31][32]. The GCD curves of all the samples have the triangular form and remains even at high current density of 50 A g −1 ), that confirm the effective ion diffusion mechanism at interiors of the nanoporous carbon materials at higher current densities.…”
Section: Electrochemical Measurementsmentioning
confidence: 62%
“…Figure 6a shows the GCD profiles of all the samples at 1 A g −1 , including the reference carbon, which are of triangular form confirming an EDLC-type charge storage mechanism. From the above result, we see that the reference sample MxP-500 shows the lowest charge discharge time whereas the MxC-Z700 shows the highest charge discharge time which confirms the maximum charge storage capacity because of the nanoporous structure [30][31][32]. The GCD curves of all the samples have the triangular form and remains even at high current density of 50 A g −1 ), that confirm the effective ion diffusion mechanism at interiors of the nanoporous carbon materials at higher current densities.…”
Section: Electrochemical Measurementsmentioning
confidence: 62%
“…BET surface area is ca. 92.4 m 2 g –1 . , The introduction of the activator K 2 CO 3 plays a significant role in developing the porosity of carbon materials. During the carbonization process, K 2 CO 3 reacts with the carbon precursor (in this case, PAM–HPC), forming volatile gases (e.g., CO 2 , H 2 O), which exit the carbon framework. , These released gases cause the formation of pores within the carbon skeleton, resulting in large specific surface area and high nitrogen uptake.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent report, we have found that KOH activation of Nelumbo nucifera (Lotus) seed results in self-nitrogendoped porous carbon materials with an ultrahigh surface area (2489.6 m 2 /g) 197) . The preparation method included the mixing of Lotus seed biochar with KOH pellet (1:1 wt.…”
Section: Carbon Materials From Activation Of Biomassmentioning
confidence: 99%